Traffic Light Regulatory System Based on Fuzzy Algorithm Using Microcontroller - Latif, Abdul; Megantoro, Prisma (Journal of physics. Conference series, 2020)
Basically, control system for traffic lights only perform control based on a fixed time. In fact, the arrival rate of vehicles at the intersection of the road is not always the same so of course congestion at the crossroads can not be controlled. This study presents a simulation control system which can perform automatic traffic light control based on vehicle arrival rate. In this control, the duration of the flame is not constant but follows the arrival rate of vehicles. The method used to control the flame duration is fuzzy logic algorithm with the Mamdani fuzzy reasoning using Matlab software. Test results based on the simulation of fuzzy logic in fuzzy MatLab toolbox show that the fuzzy logic algorithm can be used to meet the goal of optimal traffic control, the duration of a given time based on the arrival rate of vehicles. The higher rate of arrival of the vehicle, the longer the duration of a given time, and the lower rate of the arrival of the vehicle, the more briefly given time duration.